2021
DOI: 10.3390/jcm10235596
|View full text |Cite
|
Sign up to set email alerts
|

Iron Dysregulation and Frailty Syndrome

Abstract: Patients with diagnosed frailty syndrome (FS) represent a special group of patients with chronic disease. In the classic definition, frailty syndrome includes such parameters as reduced muscle strength, subjective feeling of fatigue, unintentional weight loss, slow gait, and low physical activity. Frailty syndrome leads to an increased incidence of adverse events, such as falls, hospitalizations, and the need to place patients in care and health institutions associated with the loss of independence; frailty sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Patients with diagnosed frailty syndrome represent a unique group of individuals with chronic illnesses. In the classic definition, frailty syndrome includes parameters such as reduced muscle strength, subjective fatigue, unintentional weight loss, slow gait, and low physical activity, which increase the incidence of adverse events, such as falls, hospitalizations and even death ( 36 ). Moreover, iron deficiency commonly co-occurs with depressive symptoms in older individuals ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with diagnosed frailty syndrome represent a unique group of individuals with chronic illnesses. In the classic definition, frailty syndrome includes parameters such as reduced muscle strength, subjective fatigue, unintentional weight loss, slow gait, and low physical activity, which increase the incidence of adverse events, such as falls, hospitalizations and even death ( 36 ). Moreover, iron deficiency commonly co-occurs with depressive symptoms in older individuals ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, iron deficiency frequently co-occurs with chronic inflammatory diseases ( 34 ). The sTfR has been found to significantly and positively correlate with CRP concentration ( 36 ) and antioxidant status, independently of covariates such as serum ferritin and hepcidin ( 38 ). Mild elevation of sTfR levels in multiple sclerosis patients may indicate active inflammation with ongoing oxidative damage that is not detectable through history or examination ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A recent study confirmed the relationship between reduced iron concentration and the occurrence of frailty syndrome. 20 Iron deficiency affects up to 50% of CVD patients, and its association with poor quality of life, impaired exercise tolerance, and increased mortality rates has been widely established. 21 Current European Society of Cardiology Guidelines for CVD recommend a diagnostic workup for iron deficiency in all CVD patients.…”
Section: Ironmentioning
confidence: 99%